Power relationship in human rights with dignity of the adolescent in Mexico. - OVANDO ARIAS, MATEO; Priego Álvarez, Heberto Romeo; Islas Colín, Alfredo (Cinzontle, 2024)
The complex relationship between power and dignity of adolescents in Mexico, highlighting human rights violations. Even more so is the lack of effective implementation of laws that protect adolescents, as well as the stigmatized perception that authorities have about them. Despite regulatory advances, the implementation of regulations that protect this group remains deficient, which restricts their ability to fully exercise their rights and maintain their dignity. Through a structuralist and realistic legal analysis, the study evaluates the effectiveness of the legal system and reveals significant obstacles in the application of public policies. The stigmatized perception that authorities have towards adolescents is criticized and a collaborative approach between various social actors is proposed to improve the situation. The importance of international instruments is mentioned, such as the Convention on the Rights of the Child and other covenants, which recognize specific rights for adolescents and establish protection mechanisms. Highlights the urgency of strengthening the protection of adolescent dignity, emphasizing that, although legal frameworks exist, the actual practice by institutions remains insufficient, which shows the vulnerability and the need to make effective the tangible rights of adolescents in Mexico.
Keywords: human rights; boys and girls; dignity; adolescence